Taayush in Abu Dis, Southern Hebron Mountain and Salfit - Even, Rona (Coalition of Women for Peace, 2004)
Duration: 00:15:00 Taayush is a political organization protesting the right-wing policies of Israeli government representatives, while at the same time attempting to provide a coherent and powerful civic response to violent measures adopted in the Occupied territories. The present film is focused upon the negative consequences of the building of the security wall while also documenting the inevitable and un-called for harsh response of the security forces.